MEASUREMENTS OF THE ATMOSPHERIC MINOR CONSTITUENTS AT SYOWA STATION, ANTARCTICA, IN 1986 (II) - フカボリ, マサシ; マキノ, ユキオ; タナカ, マサユキ; カワグチ, サダオ; ヤマノウチ, タカシ; FUKABORI, Masashi; MAKINO, Yukio; TANAKA, Masayuki; KAWAGUCHI, Sadao; YAMANOUCHI, Takashi (National Institute of Polar Research, 1991)
P(論文) Ground-based observations for the solar spectra were carried out to determine the column amounts of the minor constituents at Syowa Station, Antarctica in 1986. Solar spectra were measured within the spectral region from 400 to 5000(cm)^<-1> by a Fourier transform infrared spectrometer (FTIR) whose resolution is 0.125 or 0.25(cm)^<-1>. Column amounts of the gaseous constituents were determined by comparing observed equivalent widths with theoretical calculations. The total H_2O obtained by FTIR observations agreed with the results of radiosonde soundings within the observational error. The temporal variation of the total O_3 obtained by FTIR observations was quite similar to the result obtained by the Dobson spectrometer. Rapid increase of the total O_3 accompanied by the stratospheric sudden warming was clearly observed on October 21. The temporal variations of the total N_2O, CH_4 and CO_2 were also found. We examined the relation between the variations of the total column amounts and the meteorological elements. Correlation between the total column amounts of N_2O, CH_4 and CO_2 and the thickness of tropospheric air mass was quite good. departmental bulletin paper